Estuarine Fish Feeding Changes as Indicator to Mangrove Restoration Success in Seasonal Karstic Wetlands - Hernández-Mendoza, Lesli C.; Escalera-Vázquez, Luis; Arceo-Carranza, Daniel (Frontiers in Forests and Global Change, 2022)
The loss of mangrove areas due to anthropogenic activities has triggered efforts to recover or restore these ecosystems, their functions and associated diversity. Such functions include, nursery areas, and energy flow through trophic relationships for a large variety of inhabitant fish species. The food webs and trophic dynamics of estuarine fish provide important information on the food resources in mangrove ecosystems and their response to restoration processes. Nonetheless, few studies focus on using fish feeding characteristics as an approximation to assess the conservation status of these aquatic ecosystems. In this context, stomach contents were analyzed for eight species of fish inhabiting specific mangrove zones (1- Conserved Zone, and 2- Restored Zone; a zone exposed to ecological restoration processes due to impacts of anthropic activities) from the Mexican-Caribbean. Four feeding characteristics were considered: trophic guild, trophic level, feeding strategy and prey diversity. Results show that differences and changes exist in the use of food sources at the trophic level for species like Floridichthys polyommus, switching from a secondary consumer in the conserved zone to a primary consumer in the restored zone. This suggests that the mangrove’s conservation status influences the feeding characteristics of the inhabiting fish, altering the trophic dynamics of the community. Such information is relevant for mangrove restoration plans that include the analysis of fish and their prey diversity. Knowledge of the diet changes in fish serve as an important tool, easy and rapid in obtaining to determine the conservation status of these aquatic ecosystems and allowing evaluations of restoration success from a functional perspective.